Natural Flavonoid Pectolinarigenin Alleviated Hyperuricemic Nephropathy via Suppressing TGFβ/SMAD3 and JAK2/STAT3 Signaling Pathways - Ren, Qian; Wang, Bo; Guo, Fan; Huang, Rongshuang; Tan, Zhouke; Ma, Liang; Fu, Ping (Frontiers in Pharmacology, 2022)
Natural flavonoid pectolinarigenin (PEC) was reported to alleviate tubulointerstitial fibrosis of unilateral ureteral obstruction (UUO) mice in our previous study. To further investigate the nephroprotective effects of PEC in hyperuricemic nephropathy (HN), adenine and potassium oxonate induced HN mice and uric acid-treated mouse kidney epithelial (TCMK-1) cells were employed in the study. As a result, PEC significantly lowered serum uric acid level and restored hyperuricemia-related renal injury in HN mice. Meanwhile, PEC alleviated inflammation, reduced FABP4 level, and attenuated fibrosis in the kidneys of HN mice and uric acid-treated TCMK-1 cells. Mechanistically, PEC inhibited the expression of TGF-β as well as the phosphorylation of SMAD3 and STAT3 in vivo and in vitro. In conclusion, our results suggested that PEC could inhibit the activation of SMAD3 and STAT3 signaling to suppress inflammation and fibrosis, thereby alleviate HN in mice.